Cold Stress as Corrector of Functional Architecture of Blood Brain Barrier in Aged Rats. Part 1. Fractal Analysis - Babiychuk, V. G.; Marchenko, V. S.; Babiychuk, G. A. (Problems of Cryobiology and Cryomedicine, 2012)
Applying radioisotope methods, those of electron microscopy and fractal morphometry the functional architecture of blood brain barrier (BBB) of 24 month-old rats has been studied. It has been shown that pain and periodic cold effects of low positive and ultralow negative temperatures have structural and functional features of the response of BBB elements which are statistically and significantly found with the indices of fractal dimension (D). At pain and extreme cryoeffects the .D value of brain capillary endothelium monotonously increases up to ~1.5. At periodic effect of hypothermia .D is of manifested rhythmics (anti-persistent periods are found between persistent ones), testifying to a rise in plasticity, but preservation of structure resistance. When cooling the BBB permeability is increased for noradrenalin (if D~1.3) and acetyl choline (at D~1.7).